1995
DOI: 10.1002/cpe.4330070204
|View full text |Cite
|
Sign up to set email alerts
|

Computational similarity

Abstract: SUMMARYThe paper enunciates the principle of computational similarity, whereby calculations with the same values for certain dimensionless ratios are said to be 'computationally similar' and as a consequence have the same optimum self-speed-up and optimum number of processors. Based on a three-parameter description of the computer hardware, two dimensionless ratios, which are only a function of the problem size and the hardware parameters, completely determine the scaling. Contours of constant self-speed-up ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, predicting communication performance in terms of performance parameters provided by existing Parkbench codes is not just a function of low-level parameters, measured by simple communication benchmarks. Previous studies have shown that the analytic expression (2) fits well into parallel performance data [6,3]. Unfortunately, the fitted values of parameters turn out to be very different from those determined by the low-level benchmarks.…”
Section: Discussionmentioning
confidence: 93%
“…However, predicting communication performance in terms of performance parameters provided by existing Parkbench codes is not just a function of low-level parameters, measured by simple communication benchmarks. Previous studies have shown that the analytic expression (2) fits well into parallel performance data [6,3]. Unfortunately, the fitted values of parameters turn out to be very different from those determined by the low-level benchmarks.…”
Section: Discussionmentioning
confidence: 93%
“…Computational force has the same units, flop/byte, as an important quantity in performance analysis called computational intensity by Hockney [6,7] and others [14] and also called balance by some other authors [4,13]. Identifying it as a force allows us to think of computation in a new framework described in the next section.…”
Section: Hockney's Modelmentioning
confidence: 96%
“…first proposed by Hockney [6][7][8][9]. It treats time t as a linear function of length n, the number of data items moved.…”
Section: Hockney's Modelmentioning
confidence: 99%
“…Similarity coefficients (SC) aim at quantifying the extent to which objects resemble with each other. Many researchers have proposed plenty of meaningful binary similarity coefficients in their fields, such as ecology and biogeography , privacy‐preserving data mining , biometric areas , computational similarity , and porting scientific application . One specific example is Jaccard index , which was used to cluster ecological species.…”
Section: Introductionmentioning
confidence: 99%